2017
DOI: 10.1007/s40415-017-0417-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen during nursery stage on flower bud differentiation and early harvest after transplanting in strawberry

Abstract: Flowering is essential for fruit production. The effects of nitrogen (N) on flower bud differentiation and early harvest in strawberry are not clear. Experiments were conducted to investigate the most effective concentration of N treatment during the seedling stage and further elucidate the mechanism of flower bud differentiation in cultivated strawberry (Fragaria ananassa Duch.'Benihoppe'). The results demonstrated that T2 (treatment 2) of 0.1 g/plant was the suitable concentration for flower bud differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…IAA is the main factor responsible for inflorescence stalk elongation [18]. IAA was also controversial, as both positive and negative effects of IAA have been reported [19]. Our study showed that IAA content of buds significantly decreased from flower bud pre-differentiation to late flower differentiation.…”
Section: Discussionmentioning
confidence: 54%
“…IAA is the main factor responsible for inflorescence stalk elongation [18]. IAA was also controversial, as both positive and negative effects of IAA have been reported [19]. Our study showed that IAA content of buds significantly decreased from flower bud pre-differentiation to late flower differentiation.…”
Section: Discussionmentioning
confidence: 54%
“…The effects of hormones on flower formation is not only represented by a single hormone but also by the balance of multiple hormones (Li et al, 2019). Previous studies found that higher ratios of ZR/IAA, ABA/IAA, ABA/GA3, and ABA/IAA+GA3+ZR promote flower bud differentiation (Mo et al, 2015;Wan et al, 2018;Yan et al, 2019). AMF also promote hormone balance in host plants (Nowak, 2004;Bona et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao (2020) found that tomato fruit size and quality significantly decreased when exposed to HTHH during the fruit expansion period. Flower bud differentiation is a critical indication of final fruit production and quality (Wan et al, 2018), which is the key period from vegetative growth to reproductive growth, and environmental stress at the seedling stage can greatly affect flower bud differentiation (Li et al, 2019). However, after suffering from HTHH stress at the seedling stage, response characteristics for the flower bud differentiation of tomato remain unclear, which is of great significance for the early prediction of tomato fruit production and quality.…”
Section: Introductionmentioning
confidence: 99%